Optimisation of the biocatalytic resolution of styrene oxide by whole cells of Rhodotorula glutinis - Yeates, C.A.; Smit, M.S.; Botes, A.L.; Breytenbach, J.C.; Krieg, H.M. (Enzyme and microbial technology, 2007)
Various studies have described the optimisation of the hydrolysis of epoxides through epoxide hydrolase, however, far fewer have investigated the specific application of whole cells containing the enzyme. For this reason the enantioselective biocatalytic hydrolysis of styrene oxide by Rhodotorula glutinis UOFS Y-0653 through the use of whole cells was explored. It was found that a pH of 7.2, temperature of 45 °C and an initial substrate concentration of 50 mM led to maximum enzymatic activity. The whole cells were resistant to a changing environment. High temperatures were found to increase enzymatic activity but decrease enantioselectivity. At low temperatures (15 °C) enantioselectivity was significantly increased leading to an increase in both enantiopure substrate yield and the enantiomeric excess of both the substrate and product. No substrate inhibition was observed at initial substrate concentrations as high as 100 mM. The low deactivation energy (85.2 kJ/mol) obtained for this hydrolysis reaction suggests thermal instability of the enzyme. No significant effect on the reaction was observed when using unbuffered water instead of phosphate buffer as reaction medium.